A methodology for field-testing concepts through expert practitioner engagement. Issue 4 (4th July 2017) - Howie, P.; Bagnall, R.
Abstract: This paper presents a methodology for field-testing concepts through practitioner engagement. It was developed and trialled in a study involving the critique and reconceptualisation of the psychodramatic concept of warm-up. A critical review of the concept led to a reconceptualisation and description from which an explanatory document was drawn together as the lead statement for surveying psychodrama practitioners. The field-testing used online software to communicate with selected international participants. The lead document and survey invited critical text-based evaluative responses to the reconceptualisation. The responses were processed by selecting those with substantive critical comment and then clustering them according to a framework of criteria designed for concept evaluation. Responses were reviewed critically in the context of the overall conceptualisation and incorporated as appropriate into it. The process provided significant support for the new conceptualisation as well as critical input that led to its further improvement.